The Effect of Ethanol Extract of Grape (Vitis vinifera) as an Anti-Aging for Women in Productive Age - Siti Nadhila; Tri Widyawati (Sumatera Medical Journal, 2021)
Abstract. The aging process occurs in all parts of the body including the face. One of the factors that can influence this process is free radicals which can be suppressed by antioxidants. Grapes (Vitis vinifera) are known to contain high antioxidant compounds. This research was conducted to determine the anti-aging activity of grape ethanol extract (V. vinifera) in clay mask preparations. Grape ethanol extract obtained by maceration and formulated in clay mask dosage form with 4 concentrations namely FI (2.5%), FII (5%), FIII (7.5%) and F0 as a control. A total of 12 volunteers who met the inclusion criteria were applied to the mask every week for 4 weeks and evaluated the water content, smoothness, large pores, many blemishes and facial skin wrinkles before and after application in each treatment. Mask stability was evaluated for 12 weeks at room temperature. Data were analyzed by the Kruskal Wallis and Friedman tests. After 4 weeks of treatment, the highest changes including humidity (12.63%), pore size (50%), blemishes (57.32%) and wrinkles (75.69%) were found in FIII. While changes in skin smoothness were found in FII by 34.04%. There was a significant moisture difference between F0-FIII (p <0.05), a significant difference in evenness between F0-FI, F0-FII and F0-FIII (p <0.05), a significant difference in spots between F0-FIII (p < 0.05) and significant differences in wrinkles between F0-FIII (p <0.05). Grape ethanol extract in clay mask preparations has anti-aging activity.